2018
DOI: 10.1016/j.jacc.2018.06.064
|View full text |Cite
|
Sign up to set email alerts
|

21-Year Survival of Left Internal Mammary Artery–Radial Artery–Y Graft

Abstract: Use of LIMA + SVG has worse survival than LIMA-RA-Y in achieving total arterial revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…Studies were excluded for the following reasons: no comparison between TAR and non‐TAR strategy (n = 32), sample population derived from a previously published and included series (n = 1), and lack of propensity score matching (n = 1). Consequently, 18 articles were included in our study . Mean age and mean body mass index of the included populations were 65.6 years (±7.6) and 27.1 (±1.7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies were excluded for the following reasons: no comparison between TAR and non‐TAR strategy (n = 32), sample population derived from a previously published and included series (n = 1), and lack of propensity score matching (n = 1). Consequently, 18 articles were included in our study . Mean age and mean body mass index of the included populations were 65.6 years (±7.6) and 27.1 (±1.7).…”
Section: Resultsmentioning
confidence: 99%
“…Dividing the total number of arterial conduits used in the TAR group by the sample population, a number between 2.00 and 2.49 was obtained in five studies . The number of arterial conduits per patient in these five studies were: Bisleri 2016 = 2.42, Grieshaber = 2.04, Navia = 2.00, Royse = 2.00, and Tatoulis = 2.00). These studies were assigned to the group “two arteries in TAR”.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a large institutional cohort, we demonstrated that the survival of RAY and TAR by other techniques was not different (P = 1.000 [37] , Figure 3).…”
Section: Could Ray and Tar Achieved By Any Other Reconstruction Technmentioning
confidence: 89%